Types of Phrases in English - Nasirova Rano Azizovna (Genius Journals, 2023)
This article deals that, the usage of phrases in English due to the level of students in primary and high schools. There are given types of phrases with examples by using practical in grammar structures.
Keywords: Group of words; modifying; function; grammatical component